2006
DOI: 10.2151/jmsj.84.725
|View full text |Cite
|
Sign up to set email alerts
|

Study on Diurnal Sea Surface Warming and a Local Atmospheric Circulation over Mutsu Bay

Abstract: This study aims to investigate diurnal sea surface temperature (SST) rise in Mutsu Bay, and its relationship with the local atmospheric field. First, the characteristics of diurnal SST warming is revealed, using satellite and buoy data during 1995-2000. Satellite observations can clearly capture large diurnal SST rise that reaches a few degrees, and clarify the spatial distribution of the SST rise. The diurnal variation of the satellite-derived SST will reflect that of skin SST, which is defined as the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…SST warming over the eastern equatorial Pacific weakens Walker circulation which triggers an El Nino episode (Lau and Yang, 2003;Meyers et al, 2007). In coastal environment, SST significantly influences atmospheric condition over urban areas (Oda and Kanda, 2009;Pullen et al, 2007;Kawai and Wada, 2007;Kawai et al, 2006) that potentially affects the local weather (Yoshikado, 1992;Fujibe, 2003;Kobayashi et al, 2007). In turn, atmospheric variability, which can manifest through anomalous atmospheric convection, influences SST through cloud-radiation, wind-evaporation effect, wind induced oceanic mixing and upwelling (Kirtman and Vecchi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…SST warming over the eastern equatorial Pacific weakens Walker circulation which triggers an El Nino episode (Lau and Yang, 2003;Meyers et al, 2007). In coastal environment, SST significantly influences atmospheric condition over urban areas (Oda and Kanda, 2009;Pullen et al, 2007;Kawai and Wada, 2007;Kawai et al, 2006) that potentially affects the local weather (Yoshikado, 1992;Fujibe, 2003;Kobayashi et al, 2007). In turn, atmospheric variability, which can manifest through anomalous atmospheric convection, influences SST through cloud-radiation, wind-evaporation effect, wind induced oceanic mixing and upwelling (Kirtman and Vecchi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have concluded that the impact of SST on the sea breeze is stronger than was previously thought. Kawai et al (2006) investigated the effect on the surface wind field of a diurnal variation in SST within Mutsu Bay, Japan -a semi-enclosed sea. Diurnal SST variation is climatologically high in most semi-enclosed to fully enclosed seas such as the Mediterranean, the Arabian Sea, the Sea of Okhotsk and the Sargasso Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, Kawai and Wada (2007) estimated that the simulated heat flux from the ocean is underestimated by an average of 10 Wm −2 by midday if SST is held constant. Kawai et al (2006) analyzed SSTs from NOAA AVHRR satellite retrievals and in situ buoy data and found that for over 80 % of the days between April and September when the diurnal SST signal exceeded 1.0 K the daytime upslope wind speed remained below 5.0 ms −1 . By comparing numerical simulations of the sea breeze with and without a coupled mixed-layer ocean model, Kawai et al (2006) demonstrated that, while the sea breeze circulation does not change structurally, the circulation was weaker in the coupled diurnally varying SST run than in the uncoupled fixed SST control run.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) We need to look into the diurnal cycles of the local wind accelerations. As possible causes, Part I has suggested diurnally varying cool-air intrusion into the strait and the bay from the east, and complex distribution of land and sea with differential heating and cooling on the basis of Kawai et al (2006). To address these challenges, analyses of numerical simulation data are indispensable.…”
Section: Introductionmentioning
confidence: 99%